Jimat dan Mistisme Pengikut Tarekat Syattariyah di Sumatera Barat Abad Ke-19 M - Lathifah Anggriana; Sovi Oktavia; Ridwan Rahmansyah; Latifah Rahimah (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
This article aims to regulate the issues related to amulets and mysticism of the followers of the Syattariyah order in West Sumatra in the 19th century. The Syattariyah Order that entered and developed in West Sumatra has brought many changes in people's lives, one of which is the use of sharia-based amulets as a bulwark of self-defense and cure various diseases that are not detected with a doctor's stethoscope. This research uses historical methods through literature review of ancient manuscripts in the form of books left by the Syattariyah Order in the 19th century period and other literature relevant to the research topic. The Amulet the Power of Magic (1898), the digital collection of the British Library of London, is the primary source used among other ancient manuscripts from the relics of Surau Parak Laweh. In addition, secondary sources are also used in the form of literature from books and scientific articles that discuss amulets in Indonesia. From the results of the study, it was found that the development of the Syattariyah Order in Minangkabau was colored by a mixture of local culture with Islamic teachings so as to produce Islamic teachings that contain mystical elements, this mixture produced sharia-based amulets which are believed to be part of local wisdom that must be maintained and preserved from generation to generation.